Noncommutative analogue of Diffie-Hellman protocol in matrix ring over the residue ring - Rososhek, Semen Konstantin; Gorbunov, Evgeniy (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Abstract. Classical Diffie-Hellman protocol of the key establishment was the basis of the development of several key exchange protocols. But this protocol is not secure and it is not protected against the â€œman in the middleâ€ attack. The purpose of this article is to offer a secure and practical noncommutative analogue of the Diffieâ€“Hellman protocol that is reliably protected not only against â€œman in the middleâ€ attack but also against the quantum computer attack